'With or Without You…': Deconstructing Teleology between Philosophy and Biology. Issue 1 (July 2017) - Vitale, Francesco
Abstract : This essay constitutes the first stage of a new research project inspired by my work Biodeconstruction. Jacques Derrida and the Life Sciences . The aim of this project is to put to the test the effects that Derrida's understanding of the living as a 'telic structure' has on the life sciences.